Best Practices Pendidikan Karakter Pada Sekolah Unggulan di Bandung - Prakoso, Bagus Hary; Ramdani, Zulmi; Rahmah, Bilqisthi (Pusat Asesmen dan Pembelajaran, 2020)
Character education is an inseparable part of the program of strengthening and improving the quality of education in various aspects of life. Character education is manifested in a variety of activities and conditions that allow each school to be able to optimize the cognitive abilities of children in addition to strengthening their morals and character as a whole. Each school has advantages and good mechanisms that support the implementation of the character education program the study was conducted to explore and obtain a picture of best practices carried out by leading schools implementing the character education strengthening program (PPK). Qualitative research with a collective case study design is used in this study. There are 3 excellent schools that become research locus with 18 respondents who involved as research participants selected using purposive sampling. Exploration was implemented using the interview method, focus group discussion, and direct observation. The results showed that the implementation of character education conducted at the three schools was very effective because it was supported by various policies, concrete actions, and the consistency and seriousness of the school in supporting the program. The best practices that might be used as a model by other schools include praying together, conducting joint worship routines, rotating cults, conducting environmental love programs, literacy, and cultural love programs